Proposta educativa de enfermagem na síndrome de apneia e hipopneia obstrutiva do sono - Caniçali, Renato Alves (2015)
Introduction: The obstructive sleep apnoea syndrome (OSAS) is a chronic disease characterized by recurrent episodes of partial or total obstruction of the upper airway during sleep, despite continued respiratory efforts. Objectives: To describe the sociodemographic and clinical profile, assess gender differences and correlate body mass index (BMI) and apneas and hypopneas index (AHI) in patients with OSA. Methodology: Descriptive study carried out through consultation with records of OSA patients treated in a CPAP/BiPAP Program, in the Vitória’s Regional specialties center. Statistical analysis was performed using ANOVA one way to compare the means. After we used the Tukey test (post-hoc). The degree of correlation between variables was calculated using Pearson's correlation coefficient (r). The test Square, the Z test and Fisher's exact test were required to evaluate the relationship and the differences between the proportions of genres with the variables. To evaluate the relationship of cause and effect of variables with the genres, the simple logistic regression was used. Results: We found a predominance of OSA in men (63%), married (83.3%), aged between 51-60 years (30%), hypertension (59%), from the city of Vila Velha (24 %). The mean AHI and BMI in men and women was 48.3 ± 12.1 versus 44.97 ± 10 events / hour and 31.7 ± 5.7 versus 32.97 ± 5.9 kg / m², respectively. Women with OSA in the above 41 groups are at increased risk for OSA than men when comparing the range 21-40 years. In addition, women with grade III obesity have 4.3 times more risk to have OSA than those of normal weight. There was strong correlation between BMI and AHI in men (r=0.71) and moderate correlation in women (r=0.67). Conclusion: Patients treated at the program CPAP/BiPAP, mostly, have a similar profile to the global carrier OSAS population: predominantly men aged 51 and 60, hypertensive and with increased BMI. We also note that BMI is an important risk factor for worsening of OSA, especially in males.